Morphological changes of the jejunal mucosa in protracted diarrhea and their correlation with disease duration, weight loss and serum albumin levels - Péret-Filho,L.A. (1997)
The pathogenesis of protracted diarrhea is multifactorial. In developing countries, intestinal infectious processes seem to play an important role in triggering the syndrome. Thirty-four children aged 1 to 14 months, mean 6.5 months, with protracted diarrhea were studied clinically and in terms of small intestinal mucosal morphology. Mild, moderate or severe hypotrophy of the jejunal mucosa was detected in 82% of cases, and mucosal atrophy was observed in 12%. The intensity of the morphological changes of the jejunal mucosa correlated negatively with serum albumin levels. No correlation was detected between mucosal grading and duration of diarrhea or between mucosal grading and weight reported as percentile. After nutritional support was instituted, serial jejunal biopsies were obtained from 12 patients: five patients submitted to parenteral nutrition for 7 to 38 days, mean 17 days, and 7 patients receiving a hypoallergenic oral diet (semi-elemental formula, 3; chicken formula, 3; human milk, 1). In seven cases (58%) a progressive increase in villus height and a decrease in the number of inflammatory cells were noted. Recovery of the morphologic pattern was accompanied by clinical improvement in all patients